Sensitivity and specificity of measures of the insomnia experience: a comparative study of psychophysiologic insomnia, insomnia associated with mental disorder and good sleepers. - Kohn, L; Espie, C (2005)
STUDY OBJECTIVES: To explore proposed explanatory mechanisms in psychophysiologic insomnia by investigating the sensitivity and specificity of commonly used insomnia research tools in discriminating psychophysiologic insomnia, insomnia associated with mental disorder, and good sleepers. DESIGN: Cross-sectional, between-group comparison of responses from subjects with psychophysiologic insomnia, those with insomnia associated with mental disorder, and good sleepers to psychometrically robust self-report instruments. SETTING: Attendees at adult community outpatient clinics. PARTICIPANTS: Fifty-four adults (36 women, 18 men; average age 40 years) across 3 groups (n = 18 per group). Participants with psychophysiologic insomnia met combined Inteernational Classification of Sleep Disorders, Revised and Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria and had no history of mental disorder. Participants with insomnia associated with mental disorder satisfied the same criteria for sleep disturbance and met Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (Structured Clinical Interview for DSM-IV axis-I Disorders) criteria for depressive disorder. The majority had comorbid anxiety disorder. Insomnia duration in the groups with psychophysiologic insomnia and insomnia associated with mental disorder was around 10 years. Good sleepers served as a control group and included self-reported good sleepers with no history of sleep problems or psychiatric disorder. INTERVENTION: N/A. MEASUREMENTS AND RESULTS: Analyses of variance, adjusted for multiple comparisons, indicated no between-group differences on a measure of sleep-related stimulus control, and self-reported somatic arousal was higher in subjects with insomnia associated with mental disorder than in good sleepers or those with psychophysiologic insomnia. Subjects with insomnia associated with mental disorder and psychophysiologic insomnia had poorer sleep hygiene and were characterized by heightened mental arousal. Logistic regression indicated that "effortful preoccupation with sleep" discriminated subjects with both psychophysiologic insomnia (100% sensitivity, 94% specificity) and insomnia associated with mental disorder (100%, 100%) from good sleepers and that only depressive symptomatology discriminated insomnia associated with mental disorder from psychophysiologic insomnia. CONCLUSION: Psychophysiologic insomnia and insomnia associated with mental disorder may be on a continuum of insomnia severity, rather than categorically distinct. Insomnia associated with mental disorder may respond to psychological intervention. Factors specifically discriminating insomniacs from good sleepers require further investigation.